Spiritual Intelligence, Emotional Labour and Work-Related Burnout: Investigating the Complex Relationships - W Hassan, Nurul Hasnie Hassiza; Samy, Naresh Kumar (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Human resource (HR) managers shoulder numerous workforce restructurings to mitigate escalating problems before and after the COVID-19 pandemic and ensure business performance stability. Like other functional managers, HR managers undergo pressures that push them to high work stress, leading to work-related burnout (WBO). Although the issues are essential, the lack of highlights in media reduces research attention and fact reporting. This study explores the function of spiritual intelligence (SQ) and emotional labour strategies (deep and surface acting) in mitigating HR managers’ WBO. Methods: A stratified random sampling method and a validated self-administered online survey enabled the voluntary participation and analysis of 311 HR managers from ISO 9001-certified manufacturing companies in Malaysia. Results: The results suggest that SQ increases emotional labour deep-acting (ELDA) and limits surface-acting (ELSA), significantly reducing WBO. Testing for the indirect effects reveals that ELDA and ELSA mediate the association between SQ and WBO, which signifies the importance of emotional labour strategies. Conclusion: The findings benefit manufacturing industry management by helping them better understand the role of SQ and emotional labour strategies in reducing the escalation of WBO among HR managers. Managing directors can utilise the present study to evaluate their company’s procedures, make necessary reforms, improve workplace culture, and provide better support for the HR managers who can shoulder significant staffing management without getting into burnout. Implications for relevant industries and future research directions are proposed.